2022
DOI: 10.1136/jitc-2021-003543
|View full text |Cite
|
Sign up to set email alerts
|

G6PD functions as a metabolic checkpoint to regulate granzyme B expression in tumor-specific cytotoxic T lymphocytes

Abstract: BackgroundGranzyme B is a key effector of cytotoxic T lymphocytes (CTLs), and its expression level positively correlates with the response of patients with mesothelioma to immune checkpoint inhibitor immunotherapy. Whether metabolic pathways regulate Gzmb expression in CTLs is incompletely understood.MethodsA tumor-specific CTL and tumor coculture model and a tumor-bearing mouse model were used to determine the role of glucose-6-phosphate dehydrogenase (G6PD) in CTL function and tumor immune evasion. A link be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…2D ). It was reported that G6PD is active in lymphocytes [ 18 ] and plays a critical role in T cell anti-tumor function [ 28 ]. As expected, G6PD protein is detected in tumor-infiltrating lymphocytes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2D ). It was reported that G6PD is active in lymphocytes [ 18 ] and plays a critical role in T cell anti-tumor function [ 28 ]. As expected, G6PD protein is detected in tumor-infiltrating lymphocytes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the PRMT-related key genes included in our risk model have been demonstrated involved in tumor immune response regulation. For instance, G6PD was clarified participating in cytotoxic T lymphocytes (CTLs) activation and immune escape in epithelioid mesothelioma (Lu et al, 2022). KIF20A was closely associated with immune infiltration in clear cell renal cell carcinoma (ccRCC) (Ren et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Glucose-6-phosphate dehydrogenase (G6PD) is a rate-limiting enzyme in the pentose phosphate pathway and is involved in energy generation through the maintenance of reduced NADPH co-enzyme levels ( 51 ). Because of its key metabolic role, G6PD is also involved in tumor pathogenesis where it has been reported to modulate proliferation ( 52 , 53 ), metastasis ( 54 ), chemoresistance ( 55 , 56 ), immune activation ( 57 , 58 ), and tumor ferroptosis ( 59 ). Cell division cycle-associated 8 (CDCA8) forms part of the chromosomal passenger complex (CPC) and is necessary for the stabilization of the mitotic spindle.…”
Section: Discussionmentioning
confidence: 99%